Surgical removal of a microchip from a puppy’s spinal canal - Smith, T. J.; Fitzpatrick, N. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
A 1.6 kg, six-week-old Tibetan Terrier was admitted with a 12-hours history of acute onset of progressive tetraparesis following insertion of a microchip to the dorsal cervical region. Neurological examination indicated a lesion to the Ce1 to Ce5 spinal cord segments. Radiographic examination confirmed the intra-spinal location of a microchip foreign body at the level of the second cervical vertebra. Microchip removal was achieved following dorsal hemi-laminectomy; significant intra-operative haemorrhage was encountered. The puppy was ambulatory at day seven. Follow-up telephone interview 18 months postoperatively confirmed that the patient had made a good recovery although it had a mild residual right- sided torticollis.
Keywords: Microchip; foreign body; spine; cervical; hemi-laminectomy